Tumor-Infiltrating Lymphocytes and Programmed Death-Ligand 1 Expression in Salivary Duct Carcinoma. (11th September 2019) - Chatzopoulos, Kyriakos; Collins, Andrea; Garcia, Joaquin
Abstract: Objectives: Salivary duct carcinoma is a rare high-grade salivary gland tumor, sharing common features with invasive ductal carcinoma of the breast—particularly apocrine type. Increased density of tumor-infiltrating lymphocytes (TILs) is a favorable prognostic factor in many solid tumors and has been correlated with elevated expression of programmed death-ligand 1 (PD-L1), a targetable molecule. We investigated the prognostic role of TILs and PD-L1 expression in salivary duct carcinoma. Methods: Clinical records and archived surgical pathology material were evaluated from 28 patients with a diagnosis of salivary duct carcinoma at Mayo Clinic Rochester (between 1961 and 2007). TILs were evaluated on hematoxylin and eosin–stained slides and reported as continuous variables. Immunohistochemistry for PD-L1 (clone 22C3) was performed on unstained slides and evaluated using the Combined Positive Score (CPS). Fisher's exact test was used to assess frequency distribution differences. Log-rank test and Cox proportional hazards model were used to assess the impact of the variables on survival. Results: Twenty-eight patients had salivary duct carcinoma (age range 35-87, mean 61), and follow-up averaged 60 months (range 6-252 months). At the end of the follow-up period, 22 patients (79%) had died of salivary duct carcinoma, while remaining patients were alive (4.14%) or had died of other causes (2.7%). For the entire follow-up period, levels of TILs of 40% or more were associated with favorable overall survival (log-rank test, P = .01) and were predictors of better survival in univariate analysis (hazard ratio: 0.18, P = .02). PD-L1 expression was not significantly different between the high and low TIL groups (Fisher's exact test, P = .67). Survival analysis regarding PD-L1 expression did not yield statistically significant results (log-rank test, P = .74; hazard ratio: 0.87, P = .74). Conclusion: High TIL levels, but not PD-L1 expression as determined using the CPS, predict better survival in patients with salivary duct carcinoma.